Are current laparoscopic common bile duct exploration simulators suitably designed to capture the complexity of the technique? A review of the literature and evaluation of those available. - Aburrous, Mohamed; Shao, Marine; Bailey, Benjy; Clark, Charlotte; Clarke, Michael G.; Finlay, Ian; Cota, Allwyn; Clark, James (Minimally Invasive Therapy & Allied Technologies, 2025)
Background: Whilst endoscopic retrograde cholangiopancreatography (ERCP) remains the main line of treatment for choledocholithiasis, laparoscopic common bile duct exploration (LCBDE) offers a single-stage procedure and reduced hospital stay, cost and pressure on ERCP. However, LCBDE is a demanding technique that requires training in order to master, which could be achieved through simulation. The aim of this study was to highlight the suitability of currently available LCBDE simulators for surgical training and evaluate their practicality. Methods: Database search included Embase and Medline as well as grey literature for LCBDE simulation and training. Results: Nine dedicated simulators were identified to train on LCBDE. Five simulators were validated, of which only three are commercially available and only one model could train on laparoscopic ultrasound using augmented reality. Conclusions: Most identified LCBDE simulators are meeting basic criteria to train on the procedure steps. Synthetic models have been shown to improve training and operative performance in addition to shortening learning curves, many at low cost, especially when used within a constructed surgical curriculum program. However, more investment in development and implementation is required to meet the growing need, including training on laparoscopic ultrasound. Only one primitive virtual reality-based simulator was identified and did not meet the criteria for training.